Analisis Pengelolaan Wakaf Saham di PT. MNC Sekuritas Surabaya Melalui Aplikasi Motion Trade - M Syarifudin; Abdur Rohman (STIKes Ibnu Sina Ajibarang, 2025)
Indonesia, as the country with the largest Muslim population, has great potential in developing Islamic philanthropy, particularly through the stock waqf instrument. Stock waqf allows sharia stocks to be managed to generate dividends or capital gains, which are then distributed to social programs. This study aims to analyze the effectiveness of digital stock waqf management through MotionTrade by PT MNC Sekuritas, as well as to identify the challenges and opportunities in its implementation. The research method used is qualitative, with a field approach for data collection using semi-structured interviews, non-participant observation, and documentation at PT MNC Sekuritas Surabaya and waqf institutions such as BWI and RZI. The research results show that through the MotionTrade application, donation management is carried out based on the POAC principles (Planning, Organizing, Actuating, Controlling) in accordance with sharia, with transparency and professionalism through the philanthropic features of MotionTrade. Collaboration with trusted nazhir institutions such as BWI, RZI, and BAZNAS ensures that the donations are properly targeted, covering assistance for Gaza, orphans, healthcare services, qurban (animal sacrifice), and scholarships. However, there are still challenges such as digital literacy, resource management, and continuously evolving regulations. With proper management and cross-institutional support, stock waqf and digital philanthropic donations through MotionTrade have the potential to become strategic instruments for improving the welfare of the Muslim community in Indonesia.